Challenges in neonatal care: a case report of purpura fulminans in a 10-day-old infant - Huma Sohail; Yumna Zafar; Dua Irshad Syed; Ammarah Jamal; Amanullah Lail (SpringerOpen, 2024)
Abstract Background Purpura fulminans (PF) is a rare but severe thrombotic disorder affecting small cutaneous blood vessels. It may present as bruising and discoloration but can rapidly progress necrosis and life-threatening complications if not promptly diagnosed and treated. This paper presents a rare case of neonatal PF associated with protein C and S deficiency, highlighting the importance of prompt recognition and diagnosis. Case presentation A 10-day-old male infant presented with extensive purpura fulminans, microcephaly, and craniofacial abnormalities. Laboratory investigations revealed severe deficiencies in protein C, protein S, and antithrombin III. Treatment involved a multidisciplinary approach including antibiotic therapy, blood transfusions, and anticoagulation. Discussion Neonatal PF poses significant challenges due to its high mortality rate and potential neurological complications. Prompt diagnosis and management are crucial, although outcomes can vary. Long-term care and genetic counseling are essential for families affected by this rare disorder. Conclusion This case underscores the importance of early recognition and intervention in neonatal PF, especially in resource-limited settings. Improved strategies for diagnosis, management, and patient education are necessary to enhance outcomes and support affected families.